Hourly temperature and surface water level at the Ikpikpuk delta from 5/2012 to 11/2012 ... - Jones, Benjamin (Environmental System Science Data Infrastructure for a Virtual Ecosystem; Interdisciplinary Research for Arctic Coastal Environments (InteRFACE), 2023)
This data package includes the soil temperature and surface water level observations in 2012 at the Ikpikpuk River delta in northern Alaska. The data file consists of the observation table with both the .xlsx and .csv file formats. The files can be accessed through several software tools, like Microsoft Excel, and text editors. This is raw data from the near-surface ground temperature sensors at 15 cm (active layer) and 100 cm (permafrost) soil depth and a surface water sensor at the Ikpikpuk delta site in Alaska, US. The Ikpikpuk River delta is located on the Arctic Coastal Plain of northern Alaska. The Ikpikpuk River drains a land area of 15,330 km2, emptying into Smith Bay, and the delta is fan-shaped with an aerial extent of 106 km2 (Fuchs et al., 2018). This dataset supports the publication entitled "The thermal response of permafrost to coastal floodplain flooding" submitted to Environmental Research Letters (under review), where the observed water level is used as the upper boundary condition for the ...